Botulinum toxin A in the treatment of anal fissure - Stanković Nebojša; Mirković Darko (Vojnosanitetski Pregled)
Background. This paper presents our first experience in the treatment of primary anal fissure by injection of botulinum A toxin into the internal sphincter. Methods. The study group of the retrospective study included 12 outpatients (8 females and 4 males), mean age 42 (range 18-60). During the period 2000-2003, after unsuccessful conservative treatment, patients were treated with the injections of botulinum A toxin, 100 units on both sides of the anal fissure laterally into the internal anal sphincter (50 units on either side). The patients were clinically evaluated 3, 7, and 30 days, and 3 and 6 months after the treatment. Results. Three fissures had healed after a month, and seven after 3 months. Two remained unhealed, but asymptomatic. There was no incontinence of flatus or faeces after 3 months of the treatment. After temporary healing, two fissures relapsed after 6 months, and these patients had the adequate tonus of the anal sphincter muscles. Except for the temporary incontinence, there were neither other side-efects, nor serious complications. Conclusion. Injection of botulinum A toxin achieved good results in the treatment of anal fissure. The appropriate use makes this method safe as an alternative to surgical treatment of anal fissure.